Pilar Filosofis dan Yuridis dalam Perumusan Kurikulum Merdeka Pada Tingkat MI/SD - Rif'adina, Saidatul Fitri; Fithria, Maulida (DIKLINKO JOURNALS PUBLISHER, 2024)
The independent curriculum is the latest innovation in the education system in Indonesia which is designed to provide flexibility and autonomy to schools in developing the learning process according to the needs of students. In its formulation, this curriculum is based on two main pillars, namely the philosophical pillar and the juridical pillar. The philosophical pillar reflects the holistic and humanist goals of education, while the juridical pillar provides the legal framework that governs its implementation. This article aims to examine the relationship between the two pillars and their implications in the implementation of the independent curriculum in schools. The method used is qualitative with literature study. This analysis shows that the integration of philosophical and juridical pillars is a strong basis for creating a curriculum that is responsive to the dynamics of society and the individual needs of students. The Independent Curriculum provides freedom for educators to design and implement learning that suits the needs and potential of students, while still being guided by nationally regulated competency standards. The results of this study show that the Independent Curriculum has a strong philosophical foundation in encouraging student-centered education, while adhering to a juridical framework that ensures uniformity of educational standards throughout Indonesia.